0
$\begingroup$

I am wondering how to understand a part of the summation notation used to show that the harmonic series $\sum_{n=1}^{\infty}\frac{1}{n}$ diverges.

Let $(s_{N})_{N}$ be the sequence of partial sums associated to the Harmonic series. To see how this sequence diverges, consider the following for every $n\in \mathbb{N}$:

$\sum_{n=2^{m-1}+1}^{2^{m}}\frac{1}{n}\geq \sum_{n=2^{m-1}+1}^{2^{m}}\frac{1}{2^{m}}=\frac{2^{m}-(2^{m-1}+1)+1}{2^{m}}=\frac{1}{2}$

Then:

$s_{2^{m}}= \sum_{n=1}^{2^{m}}\frac{1}{n}=\sum_{r=1}^{m}\left ( \sum_{n=2^{r-1}+1}^{2^{r}}\frac{1}{n} \right ) \geq \sum_{r=1}^{m}\frac{1}{2}=\frac{m}{2}$

which is unbounded and hence divergent.

The part $ \sum_{n=1}^{2^{m}}\frac{1}{n}=\sum_{r=1}^{m}\left ( \sum_{n=2^{r-1}+1}^{2^{r}}\frac{1}{n} \right )$ is where I don't understand. I am not super strong with summation algebra/properties and so I am not sure how this sum became two sums.

$\endgroup$
1
$\begingroup$

I don't think it's really clear in the sigma notation, so we need to prove it

For every sequence $f(k)$, we have $$\sum^{n-1}_{s=0}\;\;\sum^{2^{s+1}-1}_{k=2^{s}}f(k)=\sum^{2^{n}-1}_{k=1}f(k) .$$

Proof using telescopic identity.

$$\sum^{n-1}_{s=0}\;\;\sum^{2^{s+1}-1}_{k=2^{s}}f(k)= \sum^{n-1}_{s=0}\;\;[\sum^{2^{s+1}-1}_{k=0}f(k) - \underbrace{\sum^{2^{s}-1}_{k=0}f(k)}_{g(s)}]= \sum^{n-1}_{s=0} g(s+1)-g(s) = g(n)-g(0) =\sum^{2^{n}-1}_{k=1}f(k). $$

Ps: with that identity we can prove the cauchy condensation test: Let $(x_n)$ be a decrescent sequence of positive terms, then $\sum x_k$ converges $ \Leftrightarrow $ $\sum 2^k.x_{2^k}$ converges. And use it to show that the Harmonic series is divergent (and many other series)

$\endgroup$
  • 1
    $\begingroup$ Thank you for giving me the general case for sequences! $\endgroup$ – numericalorange Jan 20 '18 at 3:58

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.